A losing battle? Women's sport pre- and post-COVID-19. Issue 3 (27th May 2021) - Bowes, Ali; Lomax, Lucy; Piasecki, Jessica
ABSTRACT : Research question: In 2019, women's sport was reported as being on the rise. Increased participation rates, media coverage, investment and support were evident. Following the spread of COVID-19 across the globe, which halted most forms of competitive sport, there were repeated concerns about the future of women's sport. This research aims to document elite sportswomen's perceptions of the state of women's sport pre-COVID-19 and the possible impact moving forwards. Research methods: Ninety five responses from an online, anonymous, qualitative questionnaire completed by elite sportswomen mainly based, in the UK, on the impact of COVID-19 on women's sport were collected. Data were subject to a thematic analysis, to determine key concerns, and the frequency data of responses were quantitatively recorded. Results and findings: Most sportswomen felt that women's sport was on an upward trajectory, but many juxtaposed that against inequality compared to men's sport in terms of media coverage and finance. There were concerns that the subordinate position women's sport, with less resources and support, will have severe implications post-COVID-19. However, there were considerations that a pause in sport would allow for personal development, increased participation upon sports return and space for a reconfiguration of sport. Implications: Those involved in sport are encouraged to think more critically about progress narratives in women's sport. We caution that these hide perpetual, structural and symbolic inequalities and propose that they are positioned more coherently within wider gender equity agenda. This is a process that will require widespread cultural change.